Hypertension and human immunodeficiency virus: A paradigm for epithelial sodium channels? - Mutengo, Katongo H.; Masenga, Sepiso K.; Mwesigwa, Naome; Patel, Kaushik P.; Kirabo, Annet (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is a risk factor for end organ damage and death and is more common in persons with HIV compared to the general population. Several mechanisms have been studied in the pathogenesis of hypertension. Current evidence suggests that the epithelial sodium channel (ENaC) plays a key role in regulating blood pressure through the transport of sodium and water across membranes in the kidney tubules, resulting in retention of sodium and water and an altered fluid balance. However, there is scarcity of information that elucidates the role of ENaC in HIV as it relates to increasing the risk for development or pathogenesis of hypertension. This review summarized the evidence to date implicating a potential role for altered ENaC activity in contributing to hypertension in patients with HIV.